STUDI KUALITAS MIKROBIOLOGI AIR SUNGAI CIDURIAN - Hasanuddin; Franita Leonard; Wahyuni (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Many kinds of microbes are found in the water environment, to maintain water quality, it is necessary to identify the level of water pollution. Water sampling was carried out downstream of the Maja waters of the Cidurian River. Analysis of the value of microbiological parameters is carried out in a laboratory that has been accredited by KAN. The method in this study is descriptive quantitative, namely comparing the results of the analysis of water microbiological parameters with the established quality standards. Based on PP No. 22 of 2021 concerning the Implementation of Environmental Protection and Management, the concentration of fecal coliform has exceeded the limit of quality standards that have been set.